2022
DOI: 10.3390/w14152315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Environmental Factors on Diatom β Diversity (Bacillariophyta) and the Value of Diatom Indices and Sampling Issues

Abstract: Human impacts and environmental climate changes have led to a progressive decline in the diversity of diatoms in lakes in the recent past. The components of β diversity (e.g., species turnover and nestedness) and underlying factors are still poorly understood. Here, we report an investigation of two alternative approaches—beta diversity (β diversity) partitioning and local contribution to β diversity (LCBD)—including their responses to selected environmental factors and representativeness of samples in estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
3
0
3
Order By: Relevance
“…One of the most important functions of springs is to provide habitat conditions (refuges) for freshwater algae appropriate for a given area [7,8]. Springs, as with many other inland waterbodies, are threatened by directnutrient enrichment, forestry practices, agriculture pressure, and indirect factors-climate change [4,5,7,33]. Recently observed environmental changes of anthropogenic origin are associated with the steady establishment of new relationships between the environment and ecological communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important functions of springs is to provide habitat conditions (refuges) for freshwater algae appropriate for a given area [7,8]. Springs, as with many other inland waterbodies, are threatened by directnutrient enrichment, forestry practices, agriculture pressure, and indirect factors-climate change [4,5,7,33]. Recently observed environmental changes of anthropogenic origin are associated with the steady establishment of new relationships between the environment and ecological communities.…”
Section: Discussionmentioning
confidence: 99%
“…Higher values were found in the spring in the Krzemianka nature reserve (source located on the national road S8) and the spring in the Jaroszówka catchment in Białystok (located in the vicinity of a former landfill) [13]. Interdisciplinary studies have shown the increasing impact of climate change on springs' water chemistry, resulting in an uncommon dangerous decline in biodiversity [33]. The diversity and distribution of diatoms (Bacillariophyta) is mainly driven by environmental conditions, and their assemblages are particularly interesting for considering the scale of the geographical distribution of individual species [7].…”
Section: Discussionmentioning
confidence: 99%
“…Вплив антропогенного забруднення на водні екосистеми оцінюють за різними показниками, проте, обов'язково враховують автотрофну ланку -фітопланктон. Доцільність використання фітопланктону як ефективного індикатора стану водойми детально обґрунтована багатьма авторами (Van Dam et al, 1994;Barinova et al, 2015;Barinova et al, 2019;Eliasz-Kowalska et al, 2022;Bilous et al, 2023;Shelyuk, 2023). Без сумніву, структура угруповань фітопланктону перебудовується внаслідок коливань хімічного складу води та конкурентної взаємодії між видами різних відділів за ресурси середовища.…”
Section: вступunclassified
“…Біоіндикаційний аналіз здійснено з урахуванням індикаторних характеристик водоростей (Van Dam et al, 1994;Barinova et al, 2019). Обговорення Оцінювання стану водних екосистем за видами-індикаторами здійснено багатьма авторами (Barinova et al, 2015;Barinova et al, 2016;Barinova et al, 2019;Eliasz-Kowalska et al, 2022;Shcherbak et al, 2023;Bilous et al, 2023;Shelyuk, 2023). Вони аналізують переваги і недоліки індикаційних підходів.…”
Section: вступunclassified
See 1 more Smart Citation